How to feed friends and influence people : - Parker, Milton (John Wiley & Sons, Inc., 2005)
Full of insightful wisdom, hilarious anecdotes, and tasty recipes, How to Feed Friends and Influence People tells the savory story of the Carnegie Deli, home of the world-famous gargantuan sandwich. Revealing the core business principles that have made the deli such a success, the book explains why and how the Carnegie became the delicatessen of choice for presidents, celebrities, at least one sultan, and millions of other (extremely) hungry diners from around the world. More than just a delightful and delicious tale of business success, this fascinating and funny book covers the delis history, shows you how to make a real Brooklyn egg cream, and piles up loads of New York history. So get cooking!